PRODUKTIVITAS DAN EFISIENSI BEBERAPA PABRIK KAYU LAPIS DI SUMATRA SELATAN DAN KALIMANTAN SELATAN - Akub J Abdurachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Development of plywood industries should not be rated from the increase of ply mill number and the production aspects alone, but there is other indicators that need be taken into consideration such as productivity and efficiency factors. High productivity and efficiency would bring more profit to the company and save the existing national resources.In this report some results of productivity analysis is presented based on ratio of actual production over break even point (BEP) production level, and efficiency analysis is presented based on ration of actual production over production capacity level, ratio of output value over input value, and added value of logs processed into plywood criteria.Based on criteria as mentioned above it can be concluded that all six visited plymills on the average have fairly high productivity and efficiency, but utilization rate of existing production capacity is still low. The average ratio of actual production over BEP production is 2.48 with range 1.35 3.28 (coefficient of variation 29 %), the average ratio of actual production over production capacity is 0.64 with range 0.25 0.91 (coefficient of variation 50 %), the average ratio of output value over input value is 1.27 with range 1.071.38 (coefficient of variation 10 %), while the average of added value of logs to plywood is 70 % with range 17 % -112 % (coefficient of variation 21 %).